Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine which point lies on the circle represented by the equation [tex]\(x^2 + (y - 12)^2 = 25^2\)[/tex], we need to check if each point satisfies this equation:
1. Point A: [tex]\((20, -3)\)[/tex]
- Substitute [tex]\(x = 20\)[/tex] and [tex]\(y = -3\)[/tex] into the circle equation:
[tex]\[ 20^2 + (-3 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 20^2 + (-15)^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 400 + 225 = 625 \][/tex]
Since [tex]\(400 + 225 = 625\)[/tex], point A satisfies the equation.
2. Point B: [tex]\((-7, 24)\)[/tex]
- Substitute [tex]\(x = -7\)[/tex] and [tex]\(y = 24\)[/tex] into the circle equation:
[tex]\[ (-7)^2 + (24 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 49 + 12^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 49 + 144 = 625 \][/tex]
Since [tex]\(49 + 144 = 193\)[/tex], point B does not satisfy the equation.
3. Point C: [tex]\((0, 13)\)[/tex]
- Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = 13\)[/tex] into the circle equation:
[tex]\[ 0^2 + (13 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 0 + 1^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 0 + 1 = 625 \][/tex]
Since [tex]\(1 \neq 625\)[/tex], point C does not satisfy the equation.
4. Point D: [tex]\((-25, -13)\)[/tex]
- Substitute [tex]\(x = -25\)[/tex] and [tex]\(y = -13\)[/tex] into the circle equation:
[tex]\[ (-25)^2 + (-13 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 625 + (-25)^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 625 + 625 = 625 \][/tex]
Since [tex]\(1250 \neq 625\)[/tex], point D does not satisfy the equation.
Given the calculations, we can confirm that point [tex]\((20, -3)\)[/tex] lies on the circle.
So, the correct answer is:
A. [tex]\((20,-3)\)[/tex]
1. Point A: [tex]\((20, -3)\)[/tex]
- Substitute [tex]\(x = 20\)[/tex] and [tex]\(y = -3\)[/tex] into the circle equation:
[tex]\[ 20^2 + (-3 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 20^2 + (-15)^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 400 + 225 = 625 \][/tex]
Since [tex]\(400 + 225 = 625\)[/tex], point A satisfies the equation.
2. Point B: [tex]\((-7, 24)\)[/tex]
- Substitute [tex]\(x = -7\)[/tex] and [tex]\(y = 24\)[/tex] into the circle equation:
[tex]\[ (-7)^2 + (24 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 49 + 12^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 49 + 144 = 625 \][/tex]
Since [tex]\(49 + 144 = 193\)[/tex], point B does not satisfy the equation.
3. Point C: [tex]\((0, 13)\)[/tex]
- Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = 13\)[/tex] into the circle equation:
[tex]\[ 0^2 + (13 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 0 + 1^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 0 + 1 = 625 \][/tex]
Since [tex]\(1 \neq 625\)[/tex], point C does not satisfy the equation.
4. Point D: [tex]\((-25, -13)\)[/tex]
- Substitute [tex]\(x = -25\)[/tex] and [tex]\(y = -13\)[/tex] into the circle equation:
[tex]\[ (-25)^2 + (-13 - 12)^2 = 25^2 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 625 + (-25)^2 = 25^2 \][/tex]
Squaring the values:
[tex]\[ 625 + 625 = 625 \][/tex]
Since [tex]\(1250 \neq 625\)[/tex], point D does not satisfy the equation.
Given the calculations, we can confirm that point [tex]\((20, -3)\)[/tex] lies on the circle.
So, the correct answer is:
A. [tex]\((20,-3)\)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.